CCD DETECTOR IN TV STANDARD WITH SMALL EXPOSURE TIME - Shahrukhanov, O. S.; Yushchenko, A. V.; Techuk, O. (Одеські астрономічні публікації, 2017)
We constructed CCD-device working in TV standard. The exposure time can be changed from 1 to 16 TV frames. We report the results of test observations with new CCD-device and discuss the possible types of observations with this device.